La réception surréaliste de Simone Weil. Simone Weil et Georges Bataille - Ghitti, Jean-Marc (Labyrinth, 2024)
Despite her hostility to surrealism, Simone Weil received a paradoxical reception in the work and thought of Georges Bataille. From this point onwards she has attracted the interest of psychoanalysis up to the present day. After their meeting and exchanges at the beginning of the 1930s, Bataille wrote a novel in which he created a portrait of Simone Weil and asks, through her, questions which served to develop and enrich the next stages of his theoretical constructions. This pathway to progress through reference to Simone Weil has often gone unnoticed. However, it deserves to be reconstituted because it brings a disturbing light that Weil would not have approved but that could help us to renew our understanding of her personality and her work.